Performance of NIRCam on JWST in Flight. (1st February 2023) - Rieke, Marcia J.; Kelly, Douglas M.; Misselt, Karl; Stansberry, John; Boyer, Martha; Beatty, Thomas; Egami, Eiichi; Florian, Michael; Greene, Thomas P.; Hainline, Kevin; Leisenring, Jarron; Roellig, Thomas; et al.
Abstract: The Near Infrared Camera for the James Webb Space Telescope (JWST) is delivering the imagery that astronomers have hoped for ever since JWST was proposed back in the 1990s. In the Commissioning Period that extended from right after launch to early 2022 July, NIRCam has been subjected to a number of performance tests and operational checks. The camera is exceeding prelaunch expectations in virtually all areas, with very few surprises discovered in flight. NIRCam also delivered the imagery needed by the Wavefront Sensing Team for use in aligning the telescope mirror segments.